The Exarchate as an element of the Bulgarian national policy at the turn of the 20th century - Rubacha, Jarosław (Balcanica Posnaniensia. Acta et studia, 2010)
The article examines the role of the Bulgarian Orthodox Exarchate as a key instrument in the implementation of Bulgaria’s national aspirations at the end of the nineteenth and the beginning of the twentieth century. The author situates the issue within a broad historical context – from the fall of the medieval Bulgarian state and centuries of Ottoman domination to the processes of national revival, during which the struggle for ecclesiastical independence became an integral part of the emancipation movement. The aim of the study is to demonstrate how the Exarchate – established in 1870 by a sultan’s firman – transformed from a purely religious institution into a tool of Bulgaria’s national and cultural policy. Rubacha analyzes its organizational structures, networks of schools and parishes in Macedonia and Thrace, and the influence of Exarch Joseph I on the consolidation of Bulgarian national consciousness in regions disputed with Greece and Serbia. The research is based on archival and printed sources, including Exarchate documents, diplomatic reports, Bulgarian, Russian, and Western European studies, as well as literature on the Macedonian question. The author applies historical and comparative methods to reveal the complex relationship between state policy and church activity. The article concludes that the Exarchate became not only a symbol of religious independence but also an effective instrument for realizing the Bulgarian national idea. Through the development of education, parish networks, and missionary work, it successfully promoted national consolidation among Bulgarians living beyond the state’s borders. The dissolution of the Exarchate following the Balkan Wars in 1913 marked a significant weakening of Bulgaria’s cultural and political presence in Macedonia, with long-term consequences for the future of the Bulgarian national movement.